2015
DOI: 10.1111/joss.12181
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sensory Characteristics of Wood by Consumers and Trained Evaluators

Abstract: The increase in wood consumption has led to the search for species that guarantee a volume of production and the least possible environmental impact. It, therefore, becomes necessary to investigate the reason behind consumer choices for certain types of wood. The designer is essential in this interpretation of reasons that lead the user to opt for a product, transforming subjective preferences into tangible design characteristics. This article presents research that investigated users' tactile and visual perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
(17 reference statements)
1
9
0
2
Order By: Relevance
“…Prior Previous work has shown that consumer panels can provide comparable discrimination ability as trained descriptive panels, given sufficient panel size (Ares, Bruzzone, & Gimenez, 2011). As expected, the naïve panel used here displayed an uncalibrated use of the performance rating scale (Figure 4), with high variability in panelists ratings at each load voltage input level.…”
Section: Discussionsupporting
confidence: 69%
“…Prior Previous work has shown that consumer panels can provide comparable discrimination ability as trained descriptive panels, given sufficient panel size (Ares, Bruzzone, & Gimenez, 2011). As expected, the naïve panel used here displayed an uncalibrated use of the performance rating scale (Figure 4), with high variability in panelists ratings at each load voltage input level.…”
Section: Discussionsupporting
confidence: 69%
“…Un excelente indicador para predecir el consumo de un producto es la preferencia del consumidos; siendo éste un factor clave en los lanzamientos de nuevos productos alimenticios en el mercado (AINIA, 2016). El Mapa de Preferencias (PM) se define como una técnica de investigación de mercado, que utiliza diferentes herramientas estadísticas para ilustrar gráficamente las relaciones entre los gustos del consumidor y los datos sensoriales del panel utilizado, que además permite identificar y cuantificar los atributos sensoriales del producto, influyen en la preferencia de una categoría de estos bienes, así como identificar nuevos nichos de mercado; además que se usan en el desarrollo de productos y marketing sensorial para determinar los impulsores del agrado (Hwang & Hong, 2015;Jervis et al, 2016), calidad y optimización del producto (Delgado y Guinard, 2011;Neely et al, 2010), y la introducción de nuevos productos en un espacio en blanco en un mapa (De Morais & Pereira, 2015). La base de esta técnica es la aplicación de pruebas sensoriales, ya que son herramientas eficientes para evaluar la aceptación comercial del producto y determinar atributos ideales para este (Ares et al, 2013;Berget, 2018).…”
Section: Introductionunclassified
“…Preference maps have been used extensively for many types of sensory marketing and product development studies for determining drivers of liking (Hwang & Hong, ; Jervis et al, ; Kim & Kim, ; Kim, Lee, Kwak, & Kang, ; Villamor, Daniels, Moore, & Ross, ; Withers et al, ), product quality and optimization (Delgado and Guinard, ; Lawless, Threlfall, Meullenet, & Howard, ; Mahanna & Lee, ; Neely, Lee, & Lee, ), and the introduction of new products into a blank space on a map (de Morais & Pereira ; Donadini & Fumi, ). Delgado and Guinard, , Zhang et al (), Leksrisompong, Lopetcharat, Guthrie, and Drake (), and Paulsen, Næs, Ueland, Rukke, and Hersleth () interpreted a preference map based only on its configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical package cluster (SPC) analysis methods, such as hierarchical clustering methods indicated generally (de Morais & Pereira, ) or specifically, such as Ward's (Childs & Drake, ; Felberg, Deliza, Farah, Calado, & Donangelo, ; Mahanna & Lee, ; Sabbe, Verbeke, Deliza, Matta, & Van Damme, ; Sinesio et al, ; Villamor et al, ) or complete linkage (Liggett, Drake, & Delwiche, ), and more global or partitial clustering such as the k‐means method (Cherdchu & Chambers, ; Jervis et al, ; Resano, Sanjuán, & Albous, ), have been applied to data sets purposely to cluster consumers together who have similar liking patterns. Preference maps are then created, in hopes of identifying the product characteristics that are most liked for each consumer cluster.…”
Section: Introductionmentioning
confidence: 99%